How can the risk from the mismatch between inflation rates in mortgage and labor markets be mitigated? (2017)
This paper proposes a financial instrument to mitigate the risk of a mismatch between inflation and wage variations that would affect the repayment of inflation-indexed mortgages in relatively high inflation economies, where housing finance is at an incipient phase of its development. In particular, using the Argentine experience in 2016-2017, and the empirical evidence of the two preceding decades, three Swap/insurance options are proposed and simulated that would allow the debtors to limit their exposure to inflation.